PENINGKATAN LITERASI MASYARAKAT TENTANG PENGGUNAAN SUNSCREEN SEBAGAI UPAYA PENCEGAHAN PHOTOAGING DI KELURAHAN ANDUONOHU KENDARI - Astrid Indalifiany; Asniar Pascayantri; Vica Aspadiah; Rahmat Muliadi; Adibah Nailal Husna; Nabilah Dwijayanti Suleman; Nur Halimah Mutmainah; Sitti Ruhiyat; Tri Wilda Bahir; Atia Fauziah; Sitti Nurjannah; Azzahra Asmaya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
High ultraviolet (UV) exposure in tropical regions increases the risk of premature skin aging (photoaging), while public awareness regarding proper sunscreen use remains limited. This community service program aimed to improve community literacy on sunscreen use as an effort to prevent photoaging. The program was conducted in Anduonohu Village, Kendari City through door-to-door education, interactive counseling, sunscreen application demonstrations, leaflet distribution, and evaluation using post-tests and direct discussions. Educational materials included the dangers of UV exposure, selection of SPF and PA, correct sunscreen application techniques, and the importance of reapplication. The results showed an improvement in participants’ understanding and awareness regarding daily sunscreen use. Post-test evaluation indicated that 70% of participants experienced increased knowledge and behavioral changes related to sunscreen use. This activity demonstrates that personal and demonstrative educational approaches are effective in improving community skin health literacy.